THE DEVELOPMENT OF A SEAMLESS MODEL FOR PEDIATRIC THALASSEMIA CARE - Putzon, Benjar; Jansook, Naruemon; Phoomladda, Chadruedee (Journal of MCU Nakhondhat, 2024)
The purposes of this research were to 1) Study the situation of caring for children with thalassemia. 2) Develop a seamless care model for pediatric thalassemia patients and 3) Study the results of the seamless care model for children with thalassemia. Using the research and development model. The sample group studied the purposive selection was 42 pediatric thalassemia and their caregivers. The research tools used were focus group guidelines. A seamless model for pediatric thalassemia care. Knowledge assessment about thalassemia disease, self-care behavior questionnaire, quality of life questionnaire, health status record form and satisfaction assessment form. Qualitative data were analyzed by content analysis and summarize. Quantitative data were analyzed by using frequency distribution, percentage, mean, standard deviation and pair t-test. The research results found that The seamless model for pediatric thalassemia care consists of 1) The one stop service thalassemia clinic with clinic nurses, 2) Prepare a patient identification book. 3) Prepare a thalassemia disease manual. 4) Organize training to provide knowledge. 5) Develop discharge planning tools. 6) Set up a group line and forward follow-up by phone. 7) Conduct home visits. and 8) There was supervision of the use of the model. Results after implementing the model found that 1) Children with thalassemia The experimental group had an average knowledge score, self-care behavior and quality of life were higher than before the experiment, and higher than the control group Statistically significant. 2) Regarding caregivers, the experimental group had higher mean knowledge and satisfaction scores than before the experiment, and higher than the control group with statistical significance and 3) Health status, the experimental group had significantly lower mean hematocrit and serum ferritin scores than the control group.